Hounsfield Unit as a Predictor of Adjacent-Level Disease in Lumbar Interbody Fusion Surgery. Issue 1 (6th April 2022) - De Stefano, Frank; Elarjani, Turki; Warner, Tyler; Lopez, Jose; Shah, Sumedh; Basil, Gregory W.; Urakov, Timur
Abstract : BACKGROUND: Bone density has been associated with a successful fusion rate in spine surgery. Hounsfield units (HUs) have more recently been evaluated as an indirect representation of bone density. Low preoperative HUs may be an early indicator of global disease and chronic process and, therefore, indicative of the need for future reoperation. OBJECTIVE: To assess preoperative HUs and their association with future adjacent segment disease requiring surgical intervention through retrospective study. METHODS: Patients who underwent lumbar interbody fusion at a single institution between 2007 and 2016 were retrospectively reviewed. Hounsfield unit values were measured from preoperative computed tomography (CT) using sagittal images, encircling cancellous portion of the vertebral body. Patient charts were reviewed for follow-up data and adjacent-level disease development. RESULTS: A total of 793 patients (age: 56.1 ± 13.7 years, 54.4% female) were included in this study. Twenty-two patients required surgical intervention for adjacent segment disease. Patients who underwent lumbar interbody fusion and did not subsequently require surgical intervention for adjacent-level disease were found to have a higher mean preoperative HU than patients who did require reoperation (180.7 ± 70.0 vs 148.4 ± 8.1, P = .032). Preoperative CT HU was a significant independent predictor for the requirement of adjacent-level surgery after spinal arthrodesis (odds ratio = 0.891 [0.883-0.899], P = .029). CONCLUSION: Patients who underwent lumbar interbody fusion that did not require reoperation for adjacent-level degeneration were found to have a higher mean preoperative HU than patients who did require surgical intervention. Lower preoperative CT HU was a significant independent predictor for the requirement of adjacent-level surgery after spinal arthrodesis.